2017
DOI: 10.1111/jre.12489
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tongue brushing and scraping on the oral microflora of periodontitis patients

Abstract: Objective: To examine the effect of tongue cleaning with a tongue scraper (TS) or toothbrush (TB) in patients with periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
(102 reference statements)
1
6
0
5
Order By: Relevance
“…(Amou et al, ) There are various reports on the reduction of bacterial count on the tongue by tongue brushing. (Gilmore & Bhaskar, ; Laleman, Koop, Teughels, Dekeyser, & Quirynen, ; Matsui et al, ) Bordas et al (Bordas et al, ) reported that although mechanical tongue cleaning without chemical intervention can reduce bacterial load on the tongue, this effect is transient, and regular tongue cleaning is required to provide a long‐lasting reduction in bacterial numbers. However, there are some problems with the tongue brush.…”
Section: Discussionmentioning
confidence: 99%
“…(Amou et al, ) There are various reports on the reduction of bacterial count on the tongue by tongue brushing. (Gilmore & Bhaskar, ; Laleman, Koop, Teughels, Dekeyser, & Quirynen, ; Matsui et al, ) Bordas et al (Bordas et al, ) reported that although mechanical tongue cleaning without chemical intervention can reduce bacterial load on the tongue, this effect is transient, and regular tongue cleaning is required to provide a long‐lasting reduction in bacterial numbers. However, there are some problems with the tongue brush.…”
Section: Discussionmentioning
confidence: 99%
“…De Boever and Loesche correlated the amount of tongue coating and the types of surface profiles (fissures/crypts) with bacterial counts 37 ; however, other researchers did not confirm this correlation 38,39 . According to Laleman et al and Quirynen et al, MTC for 14 days reduces the amount of tongue coating but does not change the microbial load 30,40 . Thus, some authors have stated that MTC should be recommended only to patients experiencing oral malodor 17 .…”
Section: Discussionmentioning
confidence: 99%
“…38,39 According to Laleman et al and Quirynen et al, MTC for 14 days reduces the amount of tongue coating but does not change the microbial load. 30,40 Thus, some authors have stated that MTC should be recommended only to patients experiencing oral malodor. 17 However, apart from oral malodor, oropharyngeal dysphagia might be influenced by proper MTC.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 99%
“…A variety of methods to reduce tongue coating have been developed and tested to reduce oral malodor 9,10 . Mechanical removal of the tongue coating using tongue brushes or tongue cleaners is one such popular method 9,11 . Other methods include using antimicrobials, e.g., in gels or mouthwashes, or using oral tablets 10,12 .…”
Section: Introductionmentioning
confidence: 99%